Hidden targets in dermatology: In vitro and In silico inhibitory effects of common 23 dermatologic drugs on human carbonic anhydrase isoenzymes I and II - İlkay Can; Kübra Çıkrıkcı; Nahit Gençer; Harun Uslu (Journal of Enzyme Inhibition and Medicinal Chemistry)
In this study, we have aimed to determine the in vitro and in silico effects of 23 frequently used dermatologic drugs on human carbonic anhydrase I (hCA I) and II (hCA II). The inhibitory effects of the drugs on hCA I and hCA II were determined by esterase methods. The most potent inhibitors were isotretinoin for hCA I (Ki= 5.75 µM) and valaciclovir for hCA II (Ki= 5.74 µM). Ketotifen (Ki= 6.98 µM), pantoprazole (Ki= 7.16 µM) and acyclovir (Ki= 7.31 µM) were also potent inhibitors for hCA I. Isotretinoin (Ki= 6.54 µM), brivudine (Ki= 7.44 µM) and fluconazole (Ki= 7.91 µM) were also potent inhibitors for hCA II. Terbinafine hydrochloride was a weak CA inhibitor for both of these isoenzymes (Ki= 20.58 µM for hCA I and 20.32 µM for hCA I). Therefore, the drug, having a weak CA inhibitory activity, may be preferred primarily in patients with a skin disease compared to the other drugs due to important physiological functions of CAs. Molecular docking studies have shown that acitretin and isotretinoin, in particular, will inhibit hCA I at lower concentrations and have higher docking scores. For hCA II, it was shown that Isotretinoin and Ketotifen would inhibit at lower concentrations and have higher placement scores.